Effect of physical activity in children and adolescents with metabolic syndrome: systematic review protocol - Mendes , Paula de Souza (2024)
Review the scientific literature on Randomized Clinical Studies (RCT/Experimental Studies) and Non-randomized Controlled Clinical Studies (RCT/Quasi-Experimental Studies) that tested the effects of practicing physical activity as an intervention in children and adolescents with metabolic syndrome. Methods: This protocol follows the PRISMA-P (Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols Statement) recommendations for systematic review protocols. Searches were carried out in five indexed electronic databases: PubMed, Lilacs/BVS, Cochrane Library, in addition to searches in a gray literature database: Google Scholar. Descriptors indexed in the Medical Subject Headings (MeSH) and in the Health Sciences Descriptors (DeCS) were used. No limits were applied on any of the bases. The study selection process will be carried out in duplicate by two independent researchers and, if necessary, with the help of a third party to establish consensus. Duplicate articles will be excluded, titles and abstracts will be read and the full text of eligible studies will be read, in addition to manual searches in the reference lists of selected articles; in accordance with the Key Items to Report Systematic Reviews and Meta-Analyses: the PRISMA recommendation. Results: ECR and ECC will be included without language restrictions. Methodological quality will be assessed using the GRADEPRO. Discussion: This systematic review will present a current synthesis on the effects of physical activity as an intervention in children and adolescents with metabolic syndrome. This information can contribute to the scientific literature related to the area of ​​child and adolescent health and assist in the implementation of health interventions related to metabolic syndrome in children and adolescents. PROSPERO registration number: CRD42022355992.